WHOSE PRIVACY? LOBBYING FOR THE FREE FLOW OF EUROPEAN PERSONAL DATA - Hildén, Jockum Philip (AoIR Selected Papers of Internet Research, 2016)
The European institutions recently agreed on a new General Data Protection Regulation (GDPR), which addresses data sharing and information privacy challenges associated with the global flow of personal data. The new Regulation will affect all companies and organizations that process data on EU citizens, which is why the EU institutions have been intensely lobbied during the legislative process. Stakeholder involvement in the European Union’s legislative processes has previously been studied in relation to its contribution to the _throughput legitimacy_ of EU policy. Throughput legitimacy refers to how institutionalized policy processes can contribute to the overall legitimacy of political institutions in case there is a lack of policy input from the electorate. In an earlier study, a categorization of attendees to the EU’s public consultations on data protection showed that private interests are far better represented than public interests, which could be a sign of biased legislation. This paper aims to examine whether the throughput legitimacy of the legislative process was compromised by comparing the positions of lobbyists with the amendments made by the EU Council. The results from this study provide a clearer picture of the privacy perceptions of different interest groups and their influence on the GDPR. Although lobbying participation in the EU has been quite extensively researched, influence is an aspect often ignored in politics research. This paper will thus contribute to better understanding of the influence of lobbyists in the area of Internet policy.